Usage of the common mango agroindustrial waste (mangifera indica L.) in the destraction of fermentables sugars (2007)
The common mango residue (Mangifera indica L.) is a plant material that contains a large amount of lignocellulosic tissue, which can be used to obtain fermentable metabolites and fermentation products. In this work, hydrolysis treatments were applied to the common mango residue in order to convert its polysaccharides to fermentable sugar units. Acid hydrolysis was applied at three different concentrations of dilute sulfuric acid. Also, enzymatic hydrolysis was applied with two types of commercial enzymes at different concentrations under standard working conditions. Similarly, thermal hydrolysis was applied at two different temperatures. For each applied treatment, tests were carried out on the concentration of total sugars, concentration of reducing sugars, percentage of cellulose and residual hemicellulose, data with which the best treatments were determined and combinations of the best hydrolysis treatments were carried out. The most significant treatment of the individual tests was that of acid hydrolysis at 0.50% v / v sulfuric acid at 80 ° C for one hour. In the combined treatments the most significant result was the treatment in which enzymatic hydrolysis (as pretreatment) plus thermal hydrolysis and acid hydrolysis were combined. For reasons of safety in the use of reagents, as well as elimination of adverse side effects for subsequent alcoholic fermentation, the procedure involving thermal hydrolysis as a pretreatment and enzymatic hydrolysis as the main treatment was selected, as the treatment of best application in production of fermentable metabolites from common mango residues with the purpose of producing alcohol later. Subsequent studies have allowed microbial hydrolysis to be addressed with Aspergillus niger and Trichoderma viride, as well as alcoholic fermentation after hydrolytic treatment using previous studies. Simultaneous hydrolysis and alcoholic fermentation, and more recently and in execution the simultaneity of the processes by adding a recombinant yeast that has the ability to ferment five-carbon sugars.